Noncognitivism in ethics - Schroeder, Mark Andrew 1977- (New problems of philosophy, 2024)
"According to noncognitivists, when we say that stealing is wrong, what we are doing is more like venting our feelings about stealing or encouraging one another not to steal, than like stating facts about morality. These ideas challenge the core not only of much thinking about morality and metaethics, but also of much philosophical thought about language and meaning. Noncognitivism in Ethics is an outstanding introduction to these theories, ranging from their early history through the latest contemporary developments. Beginning with a general introduction to metaethics, Mark Schroeder introduces and assesses three principal kinds of noncognitivist theory: the speech-act theories of Ayer, Stevenson, and Hare, the expressivist theories of Blackburn and Gibbard, and hybrid theories. He pays particular attention both to the philosophical problems about what moral facts could be about or how they could matter which noncognitivism seeks to solve, and to the deep problems that it faces, including the task of explaining both the nature of moral thought and the complexity of moral attitudes, and the 'Frege-Geach' problem. This second edition has been revised and updated throughout. It includes new sections on expressivism as a meta-semantic argument; the rise of relational expressivism; the idea that expressivism leads us to a novel understanding of the nature of propositions; and expressivism and epistemic modals, deontic modals, probability, vagueness and truth. Schroeder makes even the most difficult material accessible by offering crucial background along the way. Also included are exercises at the end of each chapter, chapter summaries, and a glossary of technical terms, making Noncognitivism in Ethics essential reading for all students of ethics and metaethics"--